Postoperative Imaging of the Knee Extensor Mechanism - Long, Jeremiah R.; Rubin, David A. (Seminars in Musculoskeletal Radiology, 2018)
The extensor mechanism of the knee plays an important role in many movements of the lower extremity. Although its main function is to extend the knee, it also stabilizes the patellofemoral joint and resists passive flexion of the knee when landing from jumping. Pathologic conditions of the extensor mechanism can be acute or chronic, and they can negatively affect daily activities. Fortunately, many surgical treatments are available aimed at restoring function to the injured extensor mechanism. Understanding the surgical techniques and common complications of these procedures enables the radiologist to recognize expected and unexpected postoperative imaging appearances.
Keywords: knee; extensor mechanism; injuries; surgical techniques; postoperative appearance